Some frequency domain aspects of wave propagation on nonuniform lines. - Semlyen, A. (IEEE Transactions on power delivery)
Nonuniform line (NL) is the designation of a transmission line segment where the conductors are not parallel or where the sag is significant. In addition, transformers and also parts of metallic towers can be viewed as NLs. In this paper, the propagation characteristics of NLs are examined. They appear as generalizations of concepts from uniform transmission lines (ULs). It was found that an n-conductor NL has n pairs of modes and the forward and backward waves of a mode have the same propagation constants. However, the modeshapes defined by the voltages and currents of a given mode are different. For illustration, the variation with frequency of these propagation characteristics has been presented for the wide-span river crossing of an overhead transmission line.